Taking the People vs. Power Bloc Antagonism Further: On Laclau’s Populist Reason and European Left’s Political Strategy - Grlja, Dušan (Identities: Journal for Politics, Gender and Culture, 2017)
Author(s): Dušan Grlja Title (English): Taking the People vs. Power Bloc Antagonism Further: On Laclau’s Populist Reason and European Left’s Political Strategy Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 14, No. 1 (Winter 2017) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 142-147 Page Count: 6 Citation (English): Dušan Grlja, “Taking the People vs. Power Bloc Antagonism Further: On Laclau’s Populist Reason and European Left’s Political Strategy,” Identities: Journal for Politics, Gender and Culture, Vol. 14, No. 1 (Winter 2017): 142-147.